GREEN SATISFACTION MEMEDIASI PENGARUH GREEN IMAGE TERHADAP GREEN BEAUTY LOYALTY DENGAN MODERASI GREEN FUNCTIONAL BENEFIT - I Made Surya Prayoga; Made Pradnyan Permana Usadi; I Komang Suryadnya Diputra (JUIMA : JURNAL ILMU MANAJEMEN, 2026)
This study aims to analyze the effect of green image on green beauty loyalty with green satisfaction as a mediating variable and green functional benefit as a moderating variable among Sensatia Botanicals consumers in Bali. This research employs a quantitative approach with an associative–causal design. Data were collected through a questionnaire distributed to 120 respondents selected using a purposive sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results reveal that green image does not have a direct effect on green beauty loyalty but has a positive and significant effect on green satisfaction. Furthermore, green satisfaction significantly influences green beauty loyalty. The mediation test indicates that green image affects green beauty loyalty indirectly through green satisfaction, indicating a full mediation relationship. Meanwhile, green functional benefit does not moderate the relationship between green image and green beauty loyalty. These findings highlight that green satisfaction serves as a key factor in building consumer loyalty toward green products, while functional benefits are not yet a major driver of loyalty formation.